Literature Review Purchasing Decisions: Price Analysis, Online Consumer Reviews and Consumer Trust - Azis, Eliya; Hapzi Ali (International Journal of Advanced Multidisciplinary, 2023)
The Influence of Price, Online Consumer Reviews and Consumer Trust on Purchasing Decisions is a scientific article reviewing literature within the scope of Marketing Management science. This article aims to build a hypothesis regarding the relationship between the influence of variables which will be used as a reference in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online tools. The research method is literature review sourced from open access e-books and e-journals. The analysis of this article is qualitative descriptive . The results of this article are: 1) Price influences purchasing decisions; 2) Online Consumer Reviews influence Purchasing Decisions; and 3) Consumer trust influences purchasing decisions.